INDEKS KEPUASAN MAHASISWA TERHADAP LAYANAN AKADEMIK DAN NON AKADEMIK UIN WALISONGO SEMARANG - Anila Umriana; Dwimei Ayudewandari Pranatami (Jurnal Penjaminan Mutu, 2022)
Higher education as one of the places where education is held is expected to always maintain its quality and quality. To see the quality or quality of higher education management can be assessed from two indicators, namely the fulfillment of quality standards and the achievement of customer satisfaction. Universities must be able to manage their service quality system and administration because if not, the trust of higher education users will decrease as well as the quality of students as one of the university's users, so that student satisfaction measurements need to be carried out regularly to be input and improvement for the university. Student satisfaction survey was conducted on aspects of academic and non-academic services at UIN Walisongo Semarang. Academic and academic service aspects are each measured by 8 indicators. This study aims to determine the level of student satisfaction with service quality after participating in the learning process at UIN Walisongo Semarang. This study uses a quantitative approach and survey methods. The population of this survey is all students of UIN Walisongo Semarang. The results of the assessment of the student satisfaction index on academic services are as follows: the highest satisfaction is on the online guardianship indicator with an index of 2.99 and the lowest satisfaction is on the online lecture system (E-learning) indicator with an index of 2.27. Meanwhile, the results of the satisfaction index assessment on non-academic services are as follows: the highest indicators are; Religious guidance services for students (3.01), while the lowest index is; Career guidance and job information services (Walisongo Career Center) (2.69). All satisfaction results show high satisfaction criteria.